...as if it were one of them: Almirante Aragão - Garzón Serna, Felipe (Revista Crítica Histórica, 2020)
ALMEIDA, Anderson da Silva ...as if it were one of them: Almirante Aragão. Memories, silences and resentments in times of dictatorship and democracy. Rio de Janeiro: Eduff, 2017.